A Valuable and Low-Budget Process Scheme of Equivalized 1 nm Technology Node Based on 2D Materials - Yang Shen; Zhejia Zhang; Zhujun Yao; Mengge Jin; Jintian Gao; Yuhan Zhao; Wenzhong Bao; Yabin Sun; He Tian (Nano-Micro Letters)
Highlights A set of MoS2 nanosheet field-effect transistors (NSFETs) are fabricated, with two stacking nanosheet channel, in which two parallel MoS2 channels are controlled by three gate electrodes simultaneously. By building a comprehensive framework, the feasibility of replacing silicon-based complementary field-effect transistors of 1 nm node with 2D-NSFETs provides a 2D technology solution for 1 nm nodes, i.e., “2D eq 1 nm” nodes are verified. The horizontally miniaturized 2D-NSFET achieves a frequency increase of 28% at a fixed power consumption and also obtains a similar trend in 16-bit RISC-V CPU.